Expression profiling of ALOG family genes during inflorescence development and abiotic stress responses in rice (Oryza sativa L.) - Liu, Zhiyuan; Fan, Zhenjiang; Wang, Lei; Zhang, Siyue; Xu, Weichen; Zhao, Sijie; Fang, Sijia; Liu, Mei; Kofi, Sackitey Mark; Zhang, Shuangxi; Kang, Ningning; Ai, Hao; et al. (Frontiers in Genetics, 2024)
The ALOG (Arabidopsis LSH1 and Oryza G1) family proteins, namely DUF640 domain-containing proteins, have been reported to function as transcription factors in various plants. However, the understanding of the response and function of ALOG family genes during reproductive development and under abiotic stress is still largely limited. In this study, we comprehensively analyzed the structural characteristics of ALOG family proteins and their expression profiles during inflorescence development and under abiotic stress in rice. The results showed that OsG1/OsG1L1/2/3/4/5/6/7/8/9 all had four conserved helical structures and an inserted Zinc-Ribbon (ZnR), the other four proteins OsG1L10/11/12/13 lacked complete Helix-1 and Helix-2. In the ALOG gene promoters, there were abundant cis-acting elements, including ABA, MeJA, and drought-responsive elements. Most ALOG genes show a decrease in expression levels within 24 hours under ABA and drought treatments, while OsG1L2 expression levels show an up-regulated trend under ABA and drought treatments. The expression analysis at different stages of inflorescence development indicated that OsG1L1/2/3/8/11 were mainly expressed in the P1 stage; in the P4 stage, OsG1/OsG1L4/5/9/12 had a higher expression level. These results lay a good foundation for further studying the expression of rice ALOG family genes under abiotic stresses, and provide important experimental support for their functional research.